CO-WORKING AS THE COMPONENT OF THE E- ENVIRONMENT FORMING ENTREPRENEURSHIP COMPETENCE. MANAGEMENT, ON-LINE TOOLS FOR BUILDING A FREE WORKING SPACE (World Science, 2019)
The subject of the article is the study of modern trends coworking of the university. The key aspects of the co-working center on innovative activity of higher educational institutions of agrarian education are considered in the light of the main advantages and disadvantages of this occurrence. The purpose of the work is to study trends and approaches in the use of coworking in agricultural universities. From the standpoint of the scientific- pedagogical paradigm and systematic approach to the formation of entrepreneurial competence in a free space, the tasks, structure, forms and models of a co-working center oriented to the project-network and scientific- service support of innovative development of the agrarian sphere based on innovative ideas are revealed.A retrospective analysis made it possible to consider the prerequisites for the emergence of co-workings. Based on empirical research methods - questionnaires categories of people working in co-working centers of Ukraine, researched their motives of being in free space, advantages and disadvantages of working in co-working. The analysis of the relationships between the participants in the co-working process has allowed to justify the stages of formation the necessary infrastructure of the internal co-working environment. Conclusion: The peer review method has created an adequate model for the future development of the co-working center for higher education applicants and confirmed that co-working is helping to enhance the professional position of the agricultural business. On the basis of comparative analysis of infrastructure and architecture of software and hardware, mechanisms of organization of co-working present on the market of Ukraine, the key aspects of the model and e-environment of co-working in relation to innovative activity of higher educational institutions of agrarian education are highlighted.